BENEFIT OF THE INTEGRATION OF VISIBLE AND THERMAL INFRARED IMAGES FOR THE SURVEY AND ENERGY EFFICIENCY ANALYSIS IN THE CONSTRUCTION FIELD - Parente, Claudio; Pepe, Massimiliano (Journal of Applied Engineering Science, 2019)
Infrared thermography is a non-invasive and non-contact technique that provides surface temperature distribution by measuring infrared radiation emitted by a body. The instrument that can determine the surface temperature of the object indicated is the thermal-camera. Nowadays, the use of thermal imaging is increasingly widespread and its application fields are numerous, especially in the construction environment. In this way, using a modern thermal-camera, it has showed in this paper the high performance of temperature map generated by these instruments. The integration of thermal camera with optical sensors allows to obtain, by a suitable methodology, a high quality of thermal image. Indeed, taking in account large building, it is impossible to cover the whole building and at the same time acquire with a high geometric resolution in relation to the modern thermal camera. In order to identify anomalies temperature on large and modern structure, a case study of the use of thermal images building is showed in the manuscript. Indeed, the knowledge of temperature distribution on the facade of the building provides very useful information to discover many hidden conditions related to the building performance, maintenance and energy efficient. Because the construction field accounts for 40% of energy demand in Europe, the use of thermal images in this environment provides an important contribute in the analyses process of temperature archived on the buildings.
Keywords: pan-sharpening; emissivity; structure from motion; TIR; thermal images